Strategic Group Of National Cement Industry: A Case Study Of PT. Semen Indonesia TBK - Muhammad, A. Fadel; Indradi, Dimas A.; Kaltum, Umi (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2022)
The aim of this research was to produce a map of Semen Indonesia's strategy group at PT Semen Indonesia Tbk. A strategic group is a collection of firms in an industry that share a common strategy, scope of operations and resources that they use to win the competition (Hunt, 1972; Porter, 1980; in Meilic 2019) with a focus on the importance of industry strategic grouping in understanding differences among firms within an industry. The issues involved in identifying strategic clusters within industries are examined through a comprehensive review of recent research. The research method used was the case study method, which is a series of scientific activities carried out in detail and in depth to reveal an event and the activities of an entity in order to gain in-depth knowledge about the event. This research explores the strategic groups in the National cement industry with reference to the position of PT Semen Indonesia Tbk as one of the companies included as a sub-sector of the National cement industry. The results of the study show the mapping of strategic groups of the Indonesian retail industry from several national cement companies in Indonesia: PT Semen Indonesia (Persero) Tbk, PT Indocement Tunggal Prakarsa Tbk, PT Holcim Indonesia Tbk, PT Semen Baturaja, PT Cemindo Gemilang, and PT Solusi Bangun Indonesia Tbk.